Drain Management Following Distal Pancreatectomy: Characterization of Contemporary Practice and Impact of Early Removal. Issue 6 (December 2020) - Seykora, Thomas F.; Liu, Jason B.; Maggino, Laura; Pitt, Henry A.; Vollmer, Charles M.
Abstract : Objective: To explore contemporary drain management practices and examine the impact of early removal following distal pancreatectomy (DP). Background: Despite accruing evidence supporting its benefit following pancreatoduodenectomy, early drain removal after DP has yet to be explored. Methods: The American College of Surgeons' National Surgical Quality Improvement Program (ACS-NSQIP) was queried for elective DPs from 2014 to 2017. When possible, data were linked to survey responses regarding drain management from hepato-pancreato-biliary (HPB) surgeons in the ACS-NSQIP HPB Collaborative conducted in 2017. The independent association between timing of drain removal and patients' outcomes was investigated through multivariable analyses and propensity-score matching. Results: Of 5581 DPs identified, 4708 (84.4%) patients received intraoperative drains and early removal (⩽ POD3) was performed in 716 (15.2%). Drain fluid amylase was recorded on POD1 for 1285 (27.3%) patients who received drains. The overall rates of death or serious morbidity (DSM) and clinically-relevant fistula (CR-POPF) were 19.5% and 17.0%. Early removal demonstrated significantly better outcomes when compared to late removal and no drain placement for: DSM, CR-POPF, delayed gastric emptying, percutaneous drainage, length of stay, and readmission. On multivariable analysis, early removal demonstrated reduced odds of developing DSM (OR = 0.41, 95% CI = 0.26–0.65) and CR-POPF (OR = 0.33, 95% CI = 0.18–0.61) compared to no drain placement, while late removal displayed increased odds for CR-POPF (OR = 2.15, 95% CI = 1.27–3.61) when compared to no drain placement. After propensity-score matching, early removal was associated with reduced odds for CR-POPF (OR = 0.35, 95% CI = 0.17–0.73). Conclusion: Although not yet widely implemented, early drain removal after distal pancreatectomy is associated with better outcomes. This study demonstrates the potential benefits of early removal and provides a substrate to define best practices and improve the quality of care for DP. Abstract : Supplemental Digital Content is available in the text